Analysis of Factors Affecting Deforestation in Riau From 2001 To 2023 Using The ARDL Approach - Sukajaya, I Wayan Divandra Maharesandya; Utami, Efri Diah (Proceedings of The International Conference on Data Science and Official Statistics, 2025)
Forests are one of the most important elements for human life. One of Indonesia'sproblems for decades has been high rates of deforestation. Riau is the province with the highesttotal deforestation in Indonesia in the last 23 years. The government has implemented variousmeasures to achieve both short-term and long-term targets related to reducing deforestation.Therefore, this study aims to analyze the variables suspected of influencing deforestation in theshort and long term using the Autoregressive Distributed Lag. The results of the study indicatethat the variables influencing deforestation in Riau Province in the short term are the GDP of theagriculture, forestry, and fisheries sectors and forest and land fires. In the long term, thesignificant influencing variables are the GDP of the agriculture, forestry, and fisheries sectors,the implementation of Law No. 18 of 2013, and the extent of forest and land fires. Based onthese findings, in the short term, the government is expected to transform the agricultural sectoreconomy toward a more sustainable direction and halt the clearing of forest areas for oil palmplantations, especially those conducted through forest burning. In the long term, the governmentshould further strengthen the implementation of the law.